Wearable technology usage among students of the University of Debrecen - Ráthonyi, Gergely; Ráthonyi-Odor, Kinga; Szabados, György; Bács, Zoltán; Bácsné Bába, Éva (International Journal of Engineering and Management Sciences, 2023)
The lack of physical activity and the growing prevalence of a sedentary lifestyle are urgent public health problem worldwide. The problem is also typical of the young population, especially university students, who spend most of the day in a sitting position. Technological development is one of the catalysts for the rise of a sedentary lifestyle, nevertheless, thanks to this, many devices have appeared on the market that can be used to encourage physical activity. The widespread of wearable activity tracker devices – wristwatches, wristbands – among the population shows a constantly increasing trend, with a parallel increase in the amount of data collected about ourselves (step count, calories burned, heart rate). The main goal of the present study derives from the recognition of the gap in this field in the domestic sports science literature therefore our focus is on modern information technology tools in the dimension of physical activity. The aim of this study is to assess the attitudes of the university student population towards activity-tracking devices. We conducted a cross-sectional online quantitative survey (questionnaire) among DE GTK students. 340 people filled out the questionnaire correctly. In addition to descriptive statistics, parametric and non-parametric tests (Pearson's chi-square test, Fisher's exact test, t-test, Mann-Whitney test) were used to examine the relationships. The results of the statistical tests were considered significant if p